Adverse childhood experiences and maternal disability: Findings from the North Dakota and South Dakota PRAMS, 2019. (January 2022) - Testa, Alexander; Ganson, Kyle T.; Jackson, Dylan B.; Bojorquez-Ramirez, Paola; Nagata, Jason M.
Abstract: Rationale: Prior research has found adverse childhood experiences (ACEs) to be a risk factor for disability in adulthood. Moreover, accumulating evidence highlights that both ACEs and disability during pregnancy are a risk factor for both maternal and infant wellbeing. Yet, no previous work has assessed whether ACEs increase the risk of maternal disability. Objective: The current study assesses the link between maternal ACE exposure and disability. Methods: Data are from the North Dakota and South Dakota Pregnancy Risk Assessment Monitoring System (PRAMS), 2019 ( N  = 1775). Logistic regression was used to assess the relationship between accumulating ACEs and maternal disability. Results: Mothers with exposure to a greater number of ACE—notably, 4 or more ACEs— had elevated rates of several disabilities including difficulty communicating, difficulty remembering, difficulty seeing, and difficulty walking. Conclusions: Understanding the long-term health repercussions of ACEs for pregnant women and mothers is important to help inform the design and implementation of health care interventions. This study can be used to better understand the prevalence of disabilities among mothers and corroborate early life experiences as an important risk factor for disability. Highlights: Adverse childhood experiences (ACEs) carry repercussions for health. Limited research assesses the link between ACEs and disability among mothers. ACE exposure is associated with increased risk for disability among recent mothers. Maternal ACEs impacts family planning from the earliest stages of the life course.